Kinerja Pengawas Pendidikan Agama Islam dalam Meningkatkan Kompetensi Profesional Guru - Amal Faradis (Center for Religious Studies and Social Empowerment Foundation, 2022)
This article discusses the performance of Islamic Religious Education Supervisors and the professional competence of Islamic Religious Education teachers. Based on the grand tour of researchers at SMA Negeri 6 Muaro Jambi, it can be seen that the planning prepared by the supervisor has not been in accordance with the needs of the principal and the characteristics of the teacher. The main problem is why the performance of the PAI Supervisor has not been able to improve the professional competence of teachers at SMA Negeri 6 Muaro Jambi? The research method used is an evaluative qualitative research method. This study found that the performance of PAI supervisors had not been able to improve the professional competence of teachers at SMA Negeri 6 Muaro Jambi. This is due to a lack of innovation, not using appropriate approaches and methods and steps to supervise PAI, not prioritizing the main tasks of supervising or supervising PAI as part of the competence of school principals, as well as principal policies that are not in favor of teachers and employees. Artikel ini membahas tentang kinerja Pengawas Pendidikan Agama Islam dan kompetensi profesional guru Pendidikan Agama Islam. Berdasarkan grand tour peneliti pada SMA Negeri 6 Muaro Jambi terlihat perencanaan yang disusun oleh pengawas belum sesuai dengan kebutuhan Kepala Sekolah dan karakteristik guru. Permasalahan utamanya adalah mengapa kinerja Pengawas PAI belum mampu meningkatkan kompetensi profesional guru di SMA Negeri 6 Muaro Jambi? Metode penelitian yang digunakan adalah metode penelitian kualitatif evaluatif. Penelitian ini menemukan bahwa kinerja Pengawas PAI belum mampu meningkatkan kompetensi profesional guru di SMA Negeri 6 Muaro Jambi. Hal itu disebabkan oleh kurangnya inovasi, belum menggunakan pendekatan dan metode dan langkah-langkah pengawasan PAI yang tepat, belum memprioritaskan tupoksi kepengawasan atau pengawasan PAI sebagai bagian dari kompetensi kepala sekolah, serta kebijakan Kepala Sekolah yang kurang berpihak pada guru dan pegawai.